2013
DOI: 10.1089/brain.2013.0171
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Frontal and Parietal Tectocortical Attention Pathways in Spina Bifida Meningomyelocele Using Probabilistic Diffusion Tractography

Abstract: Abnormalities of the midbrain tectum are common but variable malformations in spina bifida meningomyelocele (SBM) and have been linked to neuropsychological deficits in attention orienting. The degree to which variations in tectum structure influence white matter (WM) connectivity to cortical regions is unknown. To assess the relationship of tectal structure and connectivity to frontal and parietal cortical regions, probabilistic diffusion tractography was performed on 106 individuals (80 SBM, 26 typically dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…39 In the present study, we extended these findings by associating the integrity of these pathways with lateral ventricular volume and with clinical factors related to shunt revisions. We also assessed whether DTI metrics, ventricular volume, and shunt revisions were related to IQ scores in individuals having SBH.…”
supporting
confidence: 56%
See 3 more Smart Citations
“…39 In the present study, we extended these findings by associating the integrity of these pathways with lateral ventricular volume and with clinical factors related to shunt revisions. We also assessed whether DTI metrics, ventricular volume, and shunt revisions were related to IQ scores in individuals having SBH.…”
supporting
confidence: 56%
“…We also observed that the 2 groups did not differ in FA along the frontal pathways. 39 Although our previous study did not assess the relationship between DTI metrics and ventricular volume, we hypothesized that the decrease in WM integrity was due to mechanical stretching forces during ventricular expansion in hydrocephalus. These forces spared the anterior regions but strongly affected posterior pathways.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We instead 272 A, Treble-Barna et al (54) 19 (51) 2(5) 16 (43) 28 (76) 9(24) 0 (0) 25 (37) 7(10) 36 (53) 40 (59) 8(12) 20 (29) 3(4) 60 (88) 5 (7) 0(0) 3(4) 62 (91) 3 (4) 0 (0) 68 (100) SBM-no tectal beaking 7(41) 10 (59) 3(30) 1(10) 6(60) 9(90) 1(10) 0(0) 4(23) 3 (18) 10 (59) 8 (47) 2(12) 7(41) 4 (24) 13 (77) focused on simple, obvious visual distinctions of present versus absent. The validity of this coding scheme is demonstrated by its sensitivity to differences in connectivity using diffusion tensor imaging (DTI) in a recent study on a different cohort (Williams et al, 2013). MRI abnormalities by etiology group are presented in Table 3.…”
Section: Iviethod Participantsmentioning
confidence: 99%